THE COMPLIMENT RESPONSES USED BY HERBALIFE’S MALE AND FEMALE CUSTOMERS IN SURABAYA - Y. Meiling Turangan; Samuel Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This journal mainly deals with the males’ and females’ compliment responses from Herbalife following up system. The focus of my analysis is the types of the males’ and females’ compliment responses that occurred most frequently by both genders, the differences or/and similarities  of males’ and females’ compliment responses types. To analyze the data, I used Holmes’ (1995&2006) and Wolfson’s (1989) theories. I used Lesmana’s research (2009) as well the contrast between an online communication research and an offline communication research as supporting thesis. For the                 methods, I used a descriptive qualitative approach to be supported by quantitative data in developing my research.Then, from my analysis, I found that the both male and female interlocutors tended to accept the compliments given by me as the female complimenter.